Students’ Feedback on Standards and Criteria Provided by Bangladesh Accreditation Council for Undergraduate Program of Agrotechnology Discipline in Khulna University (South Asian Journal of Agriculture, 2026)
Accreditation is the formal recognition by an administrative body that an organization or program meets specific standards of quality. Accreditation in tertiary higher education is a formal recognition process whereby an external accrediting body evaluates and affirms that an educational institution or program meets predetermined standards of quality, ensuring that it provides a credible and effective learning environment. The study was conducted in Agrotechnology discipline, Khulna University, Khulna. A pretested interview schedule was used to collect data from randomly selected 120 respondents during August-September, 2023. The students of Agrotechnology Discipline were oriented to evaluate accreditation standards and criteria provided by BAC forgiving their feedback. Out of 10 standards and 63 criteria,9 standards and 47 criteria were considered for this study. The students expressed excellent level of satisfaction regarding standard 4: Curriculum (98.61%), followed by standard-3: institutional integrity and transparency (88.30%), the first standard, governance (87.42%), which were also excellent. Student Admission & Support Services came in fourth (77.52%). However, the other standards though met a good level of satisfaction (